Medical decision making in patients with knee pain, meniscal tear, and osteoarthritis. - Suter, Lisa G; Fraenkel, Liana; Losina, Elena; Katz, Jeffrey N; Gomoll, Andreas H; Paltiel, A David (Arthritis and rheumatism, 2009)
Meniscal tears and osteoarthritis (OA) frequently coexist, but to our knowledge, no data exist to identify who will benefit from arthroscopic partial meniscectomy (APM) versus nonoperative management. Our objective was to evaluate the capability of preoperative information to predict APM outcomes in OA.
Keywords: Aged; Bayes Theorem; Decision Making; Humans; Knee Injuries; Magnetic Resonance Imaging; Menisci, Tibial; Middle Aged; Models, Biological; Osteoarthritis, Knee; Pain; Predictive Value of Tests; Preoperative Care; Prevalence; Sensitivity and Specificity; Treatment Outcome